2021
DOI: 10.1002/jclp.23241
|View full text |Cite
|
Sign up to set email alerts
|

Symptom variability in depersonalization–derealization disorder: A latent profile analysis

Abstract: Objective Depersonalization–derealization disorder (DDD) is characterized by diverse symptomatology overlapping with anxiety and dissociative disorders, but the sources of this variability are poorly understood. This study aims to determine whether symptom heterogeneity is attributable to the presence of latent subgroups. Method We applied latent profile analysis to psychometric measures of anxiety, depersonalization–derealization, and dissociation in 303 DDD patients. Results The analysis yielded evidence for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 64 publications
(112 reference statements)
0
16
0
Order By: Relevance
“…They reported that a low but significant association between depersonalization and anxiety was only apparent in those patients with low intensity depersonalization, but not in those with severe depersonalization. A more recent study ( Millman et al, 2021 ) assessed the extent to which symptom heterogeneity in DPD reflects the presence of five discrete latent classes (low-, moderate- and high DPD severity, High depersonalisation and High dissociation ( Brown, 2006 ). The authors found that anxiety was not a strong indicator of class differences within their sample.…”
Section: Over-inferencing the Self – From Aberrant Self-modelling To ...mentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that a low but significant association between depersonalization and anxiety was only apparent in those patients with low intensity depersonalization, but not in those with severe depersonalization. A more recent study ( Millman et al, 2021 ) assessed the extent to which symptom heterogeneity in DPD reflects the presence of five discrete latent classes (low-, moderate- and high DPD severity, High depersonalisation and High dissociation ( Brown, 2006 ). The authors found that anxiety was not a strong indicator of class differences within their sample.…”
Section: Over-inferencing the Self – From Aberrant Self-modelling To ...mentioning
confidence: 99%
“…DPD often co-occurs in relation to traumatic events, severe stress and are associated with symptoms of anxiety, panic, and depression ( Hunter et al, 2004 , Lyssenko et al, 2018 , Michal et al, 2016 , Millman et al, 2021 ). The prevalence of DPD is around 1–2% in the general population ( Hunter et al, 2004 ), with onset typically occurring before age 25.…”
mentioning
confidence: 99%
“…Although DDD is often categorized as a dissociative disorder, there have been arguments as to whether it fully encompasses the dissociative symptoms based on the Dissociative Experiences Scale (Carlson & Putnam, 1993; Millman et al, 2020). Classification of the disorder is important because that can influence how treatment plans are created (Millman et al, 2020). Regardless of its categorization, rarely is DDD included in the larger discourse of mental health and mental illness, especially within the field of Communication Studies.…”
Section: Embodying the (Dis)embodiment: Narrating Depersonalization-d...mentioning
confidence: 99%
“…Depersonalization-derealization disorder is generally understood as "a persistent or recurring feeling of being detached from one's body or mental processes, like an outside observer of one's life (depersonalization), and/or a feeling of being detached from one's surroundings (derealization)" (Spiegel, 2021, para 1). Onset can be triggered by a traumatic experience, specific drugs, panic, and more (Millman et al, 2020). Often, DDD is confused with other dissociative disorders, such as dissociative identity disorder (DID) and dissociative amnesia (American Psychological Association; APA, 2018).…”
mentioning
confidence: 99%
“…Transient and mild episodes of DP are relatively common in the general population, often related to everyday phenomena such as fatigue 29 , sleep deprivation 30 , or travelling to new places 31 . Temporary occurrences of depersonalization episodes have been reported by almost 50% of college students 32 34 . DP typically co-occurs with highly traumatic events, or as a symptom of anxiety, panic, and depression 28 , 30 .…”
Section: Introductionmentioning
confidence: 99%